Advances in Aerogel Composites for Environmental Remediation - Khan, Aftab Aslam Parwaz; Khan, Aftab Aslam Parwaz; Ansari, Mohammad Omaish; Khan, Anish (Elsevier Science, 2021)
Advances in Aerogel Composites for Environmental Remediation presents both contextual information aboutaerogels and details about their application in environmental remediation. A wide variety of aerogels are discussed, rangingfrom common to advanced and from natural to synthetic. By exploring ongoing research and developments in the environmentalremediation technologies using aerogel and its composites, this book addresses common day-to-day environmental problemsand presents solutions to the use of aerogel materials. The chapters discuss fabrication of various aerogel composites, alongwith their design and applications toward different environmental remediation technologies. Additionally, the properties andadvantages of aerogels are compared and contrasted to those of traditional materials. Given the consistent increase in environmental pollution, there is an urgent need to explore new materials for advances in remediationtechnology. Advances in Aerogel Composites for Environmental Remediation brings researchers and practitionersin the fields of environmental remediation, environmental science, and engineering to the forefront of remediation technologieswith a thorough breakdown of the benefits of and techniques relevant to aerogel composites. - Covers basic properties, unique properties, and fabrication techniques of aerogels, from basic silica aerogels topresent-day conventional aerogels - Discusses most of the major environmental remediation techniques and the advantages of using aerogels for theseremediation techniques in comparison to using traditional methods - Presents future prospects for utilizing aerogels in modern day-to-day life and in the fabrication of tangible new products